ANALYSIS OF DEFORMATION PROPERTIES OF TEA FABRICS WITH DIFFERENT SURFACE AND FIBROUS COMPOSITION (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The article shows that the composition of the fabric is 100% higher than that of polyester and single-layer bed fabrics, and the residual (plastic) deformation is lower than that of other bed fabrics with a support surface and fiber content.